2017
DOI: 10.1038/s41598-017-03124-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiling in the sub-silicone oil fluid after vitrectomy surgeries for refractory retinal diseases

Abstract: Silicone oil (SO) is an intraocular surgical adjuvant that reduces the surgical complications in refractory retinal diseases, although membrane and cellular proliferation is often seen even in SO-filled eyes. We hypothesised that the fluid in the space between the SO and the retina, named the “sub-silicone oil fluid (SOF)”, enhances these biological responses. We proposed a safe method for SOF extraction. We also analysed inflammatory cytokine expressions and SOF osmotic pressures from eyes with rhegmatogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In addition, previous histopathological studies of eyes that have undergone ILM peeling have suggested that damage to Mü ller glial cells following ILM peeling may be responsible for the thinning of the temporal macula [21,39] . Another study reported that the fluid between the SO and the surface of the retina in SO-injected eyes has a higher expression of proinflammatory cytokines [40,41] . It is reasonable to speculate that the ILM plays a protective role against vitreous fluid containing higher levels of proinflammatory cytokines in eyes treated with SO endotamponade and that retinas without an ILM are directly exposed to the fluid, resulting in more severe damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous histopathological studies of eyes that have undergone ILM peeling have suggested that damage to Mü ller glial cells following ILM peeling may be responsible for the thinning of the temporal macula [21,39] . Another study reported that the fluid between the SO and the surface of the retina in SO-injected eyes has a higher expression of proinflammatory cytokines [40,41] . It is reasonable to speculate that the ILM plays a protective role against vitreous fluid containing higher levels of proinflammatory cytokines in eyes treated with SO endotamponade and that retinas without an ILM are directly exposed to the fluid, resulting in more severe damage.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the hypothesis that SOF has an important role in the pathogenesis of SORVL, we analyzed the inflammatory cytokine and electrolyte contents of SOF samples. We had already reported our finding that IL-6 and TNF-α levels in SOF samples were higher in eyes with revision surgery required–PVR than in those with simple PVR needing only SO evacuations at the time of the second surgeries 7. In contrast, FGF-2, IL-10, IL-12p40, IL-8, VEGF, and TGF-β1 were higher in the SOFs of eyes with revision surgery required–PDR than in those needing simple PDR 7.…”
Section: Discussionmentioning
confidence: 78%
“…We obtained written informed consent from all participating patients. We collected SOF samples as described 7. Briefly, before the beginning of the infusion, the edge of a 25-G blunt needle was placed above the surface of the posterior retina in a SO-filled eye using a RESIGHT surgical microscope (Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[78][79][80][81][82][83] IL-6 can also stimulate corneal epithelial cells and stromal fibroblasts (and macrophages) to produce profibrotic VEGF. 78 Like most inflammatory cytokines, IL-6 is present in subretinal fluid in high titers during retinal detachment and RRD repair, 84,85 and their presence is correlated with the subsequent, development of postoperative PVR, 9 as well as being elevated in the vitreous of patients with early PVR, 38,86 and correlating with PVR severity when found in sub silicone-oil fluid, 87 but, because subretinal and vitreous IL-6 levels significantly overlap between patients with uncomplicated retinal detachment and severe or future PVR, they have limited biomarker potential.…”
Section: Interleukin-6mentioning
confidence: 99%